MO649DIAGNOSTIC TESTS OF NOVEL URINARY BIOMARKERS TO IDENTIFY EARLY STAGES OF NEPHROPATHY IN NON HYPERTENSIVE TYPE 2 DIABETIC MELLITUS. (29th May 2021) - Mahapatra, Himansu; Kulshreshtha, Bindu; Goyal, Dr Parul; Chirkara, Anubhuti; Khanna, Tripti; Singh, Anamika; Arora, Arpita; Prasad Gupta, Yadunandan; Sekhar, Venkatesan
Abstract: Background and Aims: Activation of RAS and tubulointerstitial damage might be seen in pre-albuminuria stage of diabetic nephropathy. Here, diagnostic tests of urinary Angiotensinogen, Cystatin C, Neutrophil gelatinase associated lipocalin and IL 18 have been studied in pre-microalbuminuria diabetic patients. Method: Total 952 Diabetic screened for Nephropathy (e-GFR ≥120&ACR≥30), among them 120 cases were followed up for one year. At one year they were classified in to Hyperfiltration43, Normoalbuminuria29 and Microalbuminuria48 groups. Another 63 Diabetes without nephropathy were included as controls. Hypertension, on ACEI/ARB, e-GFR<60ml/min/1.73m 2 and all Macroalbuminuria conditions were excluded. All were subjected to urine protein, ACR, HbA1c, e-GFR, along with urinary bio markers(IL-18, Cystatin-C, NGAL and Angiotensinogen). Comparative analysis of all groups, Diagnostic tests, correlation and logistic regression were analysed. Results: Urinary IL18/Cr, Cystatin /Cr. and Angiotensiogen /Cr. levels were higher in groups of hyper filtration (13.47, 12.11 & 8.43mg/g), Normoalbuminuria (9.24, 11.74&9.15mg/g) and microalbuminuria(11.59, 14.48&10.24mg/g) than controls(7.38, 8.39&1.26mg/g) but not NGAL/Cr. in all groups. High levels were significant in all except Cystatin/Cr. & IL18/Cr. in normoalbuminuria group. The AUC, sensitivity and specificity of Angiotensinogen (0.9, 90% and 80%) ACR (0.69, 40% and 100%) and e-GFR (0.6, 37 and 100%)respectively. AUC of other biomarkers viz, IL 18/cr. Cystatin/Cr and NGAL/Cr. were 0.65, 0.64 and 0.51 respectively. Angiotensinogen/Cr and IL18/Cr showed correlation with log albuminuria r-0.3 p 0.00 and r-0.28 p 0.00 respectively; NGAL with log e-GFR (r-0.28 p0.00).Multivariate logistic analysis showed Odds of contracting nephropathy is 7.5 times having higher values of Log Angio/Cr. Conclusion: Urinary Angiotensinogen has higher diagnostic value than ACR and e-GFR followed by IL 18 and Cystatin to diagnose DN at the pre-albuminuric stages but not urinary NGAL.